Exploring Household Preferences for Visualising Consumption Information: Towards Data Physicalizations to Promote Sustainable Practices - Perera, Dushani; Verdezoto Dias, Nervo; Gwilliam, Julie; Eslambolchilar, Parisa (Interacting with computers, 2025)
Abstract This paper explores household preferences for visualizing consumption data and investigates the potential of data physicalizations to enhance user engagement and promote sustainable practices within households. We conducted semi-structured interviews with thirteen households, utilizing a combination of images and low-fidelity prototypes to gain insights into participants’ preferences, ideas and feedback on visualizing consumption information. We requested participants to discuss an object in their home that symbolizes sustainability. The results revealed different emotional responses, from empathy to repulsion, triggered by different visual representations. Our findings also identified certain physical objects and locations within the household that play a role in fostering family collaboration towards sustainable practices. Participants preferred having a physical representation of their consumption data within their homes over a screen-based display. In light of these findings, we open space to consider designing physicalizations that encourage collaboration, enhance user engagement and motivate households to reduce their consumption.